Neural Correlates and Connectivity Underlying Stress‐Related Impulse Control Difficulties in Alcoholism. (8th August 2016) - Seo, Dongju; Lacadie, Cheryl M.; Sinha, Rajita
Abstract : Background: Stress triggers impulsive and addictive behaviors, and alcoholism has been frequently associated with increased stress sensitivity and impulse control problems. However, neural correlates underlying the link between alcoholism and impulsivity in the context of stress in patients with alcohol use disorders (AUD) have not been well studied. Methods: This study investigated neural correlates and connectivity patterns associated with impulse control difficulties in abstinent AUD patients. Using functional magnetic resonance imaging, brain responses of 37 AUD inpatients, and 37 demographically matched healthy controls were examined during brief individualized imagery trials of stress, alcohol cue, and neutral‐relaxing conditions. Stress‐related impulsivity was measured using a subscale score of impulse control problems from Difficulties in Emotion Regulation Scale. Results: Impulse control difficulties in AUD patients were significantly associated with hypo‐active response to stress in the ventromedial prefrontal cortex (VmPFC), right caudate, and left lateral PFC (LPFC) compared to the neutral condition ( p  < 0.01, whole‐brain corrected). These regions were used as seed regions to further examine the connectivity patterns with other brain regions. With the VmPFC seed, AUD patients showed reduced connectivity with the anterior cingulate cortex compared to controls, which are core regions of emotion regulation, suggesting AUD patients' decreased ability to modulate emotional response under distressed state. With the right caudate seed, patients showed increased connectivity with the right motor cortex, suggesting increased tendency toward habitually driven behaviors. With the left LPFC seed, decreased connectivity with the dorsomedial PFC (DmPFC), but increased connectivity with sensory and motor cortices were found in AUD patients compared to controls ( p  < 0.05, whole‐brain corrected). Reduced connectivity between the left LPFC and DmPFC was further associated with increased stress‐induced anxiety in AUD patients ( p  < 0.05, with adjusted Bonferroni correction). Conclusions: Hypo‐active response to stress and altered connectivity in key emotion regulatory regions may account for greater stress‐related impulse control problems in alcoholism. Abstract : Brain Stress Response and Impulse Control Problems in Alcohol‐Dependent Patients. The current study shows that hypoactive function and disrupted network connectivity in regions involving the ventromedial prefrontal cortex, caudate, and left lateral/dorsolateral prefrontal cortex underlie stress‐related impulse control difficulties in alcohol‐dependent patients. Additionally, they are characterized by altered connectivity with other brain areas, marked by decreased connectivity with prefrontal regulatory regions, but increased connectivity with sensory and motor regions.